Mer de Barents, Finlande, U.R.S.S., baies et mouillages à la côte de Petsamo / Service hydrographique de la marine . 1940 - France. Service hydrographique de la marine (1947)
Publication provisoire. Corr. . 1947 Relief shown by spot heights and hachures. Depths shown by bathymetric isolines and soundings.; Baie Suolavuono (Baie Bazarnaya) -- Baie de Lapinmukka (Finnmanskoe) -- Vaitolahti (Baie Vaida) -- Abords de Petsamo, Petsamonvuono, (Golfe Petchenga), et Maattivuono.; Includes 2 insets: Partie Méridionale de Patsamonvuono -- Liinahamart.; Selected lights shown in orange Color;